Mendorong Komitmen Bawahan Melalui Kepemimpinan Partisipatif - FX Supriyono (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
LEADERSHIP plays a central part in every organization, because it determines the achievement of the organization's goals. But what kinds of leadership we need today and for the future? The change in the social environment towards the civil society at this moment need to be anticipated with the participate style rather than autocratic style of leadership. By orienting the leadership towards the human aspects, it is possible to that leader applying the social skills that enable him/her creating the emotional quotient (EQ) that is very important in today's leadership.